2007
DOI: 10.1128/aem.01013-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Monolaurin Resistance in Enterococcus faecalis

Abstract: There is increasing concern regarding the presence of vancomycin-resistant enterococci in domestically farmed animals, which may act as reservoirs and vehicles of transmission for drug-resistant enterococci to humans, resulting in serious infections. In order to assess the potential for the use of monolaurin as a food preservative, it is important to understand both its target and potential mechanisms of resistance. A Tn917 mutant library of Enterococcus faecalis AR01/DGVS was screened for resistance (MIC, >10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…The increased rigidity of bacterial cell membranes may prevent the insertion of alamethicin into the phospholipid bilayer. These findings are supported by the previous studies showing that the presence of monolaurin changed the cellular saturated-to-unsaturated fatty acid ratio from 1.4 to 4.35 (7). The decrease in the S/U ratio indicated the increased fluid nature of the cell membrane of Alm r variant Efv4.2.…”
Section: Discussionsupporting
confidence: 89%
“…The increased rigidity of bacterial cell membranes may prevent the insertion of alamethicin into the phospholipid bilayer. These findings are supported by the previous studies showing that the presence of monolaurin changed the cellular saturated-to-unsaturated fatty acid ratio from 1.4 to 4.35 (7). The decrease in the S/U ratio indicated the increased fluid nature of the cell membrane of Alm r variant Efv4.2.…”
Section: Discussionsupporting
confidence: 89%
“…Electron microscopy studies observed morphological changes of bacteria growing in the presence of MAGs showing damage of the cell membrane under the influence of MAG (Bergsson et al 1998(Bergsson et al , 1999. Dufour et al (2007) discovered that in mutant strains of Ent. faecalis, the resistance to monolaurin is caused by the changes in the cell surface and thus MAG cannot penetrate the cell and reach the place where it could act.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism for the antibacterial activity of fatty acids and their derivatives has not been fully recognized, it was found that they cause damage to the cell membrane used as a permeable barrier and inhibit the transport of amino acids to the cell (Dufour et al 2007;Thormar and Hilmarsson 2007). Another hypothesis is based on the penetration of fatty acids with a short and medium chain in a non-dissociated form into bacterial cells and their dissociation inside the cells, which leads to acidification of the cell contents (Sado Kamdem et al 2008).…”
mentioning
confidence: 99%
“…The precise mode of the action against microorganisms is not yet clear and postulated several hypotheses. One hypothesis is based on the amphiphilic character of MAG molecule which aids in their penetration and incorporation into cytoplasmic membrane and subsequently disrupts the cell permeability and prevents the transportation of the nutrients (Nair et al, 2004;Dufour et al, 2007). An alternative hypothesis postulates the penetration of fatty acids and dissociated in the inner cell environment, thereby increasing the intracellular acidity (Sun et al, 1998).…”
Section: Introductionmentioning
confidence: 99%